2020
DOI: 10.1002/we.2549
|View full text |Cite
|
Sign up to set email alerts
|

Developing a systematic approach to the analysis of time‐varying main bearing loads for wind turbines

Abstract: This paper considers the time-varying loads experienced by wind turbine main bearings. Radial load trajectories based on simulated data indicate that 'looped' structures, in the form of repeating changes in radial load magnitudes and directions that form elliptical patterns, are present, which have not been described before in the literature. In order to allow these identified structures to be described and studied, an automated method for identification and parameterisation of these loops is presented, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(74 citation statements)
references
References 10 publications
2
72
0
Order By: Relevance
“…MBs are becoming recognised as an important component for which failures need to be better understood and reliability improved (Keller et al, 2016;Hart et al, 2020). MB failure rates have been reported as being as high as 30 % (Hart et al, 2019) across a 20-year lifetime, with some wind farms having reported MBs failing in less than 6 years (Sethuraman et al, 2015). Recent work which has demonstrated important and unusual load behaviours in wind turbine MBs (Hart et al, 2019;Hart, 2020) implements simplified analytical representations of the drivetrain.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…MBs are becoming recognised as an important component for which failures need to be better understood and reliability improved (Keller et al, 2016;Hart et al, 2020). MB failure rates have been reported as being as high as 30 % (Hart et al, 2019) across a 20-year lifetime, with some wind farms having reported MBs failing in less than 6 years (Sethuraman et al, 2015). Recent work which has demonstrated important and unusual load behaviours in wind turbine MBs (Hart et al, 2019;Hart, 2020) implements simplified analytical representations of the drivetrain.…”
Section: Introductionmentioning
confidence: 99%
“…MB failure rates have been reported as being as high as 30 % (Hart et al, 2019) across a 20-year lifetime, with some wind farms having reported MBs failing in less than 6 years (Sethuraman et al, 2015). Recent work which has demonstrated important and unusual load behaviours in wind turbine MBs (Hart et al, 2019;Hart, 2020) implements simplified analytical representations of the drivetrain. Such representations are necessary if this type of analysis is to be performed across large numbers of load cases, incorporated into fleet-wide modelling, or into industry standard simulation software (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations